Propuesta de un modelo de balance social corporativo aplicado a las cooperativas de transporte caso Panamericana Internacional - Suárez Sánchez, María Belén (2015)
This thesis is the development of a Social Balance Model designed by the Superintendency of Popular and Solidarity Economy that allow to analyze the Panamericana Internacional Transportation Cooperative . The thesis consists of four chapters discussed as follows: Chapter 1 raised is aimed at enhancing the importance of the Social history, the benefit thereof within the organization that allows us to know the social information to self-assess their social management as developed different models, and the impact in terms of America America in the implementation of social responsibility and a brief review of the People and Solidarity Economy in Ecuador. Chapter 2 raised is the Diagnosis of the Cooperative in which analyze from its objectives, goals, services to compliance with the regulations is required, through a SWOT analyze the important aspects that will help us to detect the need to propose a model type of Social Balance. Chapter 3 Social Balance model with which we measure proposed by qualitative indicators and quantitative indicators to determine if the cooperative is fulfilling its social responsibility, the impact for both partners and employees resulting in the Balance social Cooperative and report to the community and external and Internal social report for partners and staff.